ANALISIS PENGARUH KEPUASAN PRODUK WISATA TERHADAP LOYALITAS WISATAWAN (Studi Kasus pada Wisatawan DIY) - Nunuk Dwi Garwanti Palupi (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2017)
The purpose of this study is to examine the effect of tourism product satisfaction on tourist loyalty in Yogyakarta Special Region. The sample in this study is the tourists who visit Yogyakarta. The sampling technique used is simple random sampling and data collection using questionnaire. Based on the results of hypothesis testing using regression analysis obtained the result that there is influence of tourism product satisfaction on tourist loyalty in Yogyakarta Special Region. Keywords: customer satisfaction, customer loyalty